Association Between Metabolic Syndrome and Benign Prostate Hyperplasia (Bangladesh Journal of Medical Biochemistry, 2017)
Metabolic syndrome (MetS) is a highly prevalent complex disorder among adults worldwide which includes cardiovascular risk factors such as central obesity, insulin resistance, dyslipidemia and hypertension. MetS or its components are prevalent in patients with benign prostate hyperplasia (BPH), a common urogenital disorder of adult male with increasing age. This cross-sectional study was conducted in the Department of Biochemistry, Dhaka Medical College, Dhaka from July 2014 to June 2015 with a total of 100 subjects. Of these 50 patients of BPH attending the Department of Urology, Dhaka Medical College Hospital, Dhaka was taken as Group I and 50 age-matched apparently healthy adults was taken as Group II. According to the National Cholesterol Education Program Adult Treatment Panel (NCEP-ATP III, 2005) criteria, components of MetS as fasting plasma glucose, serum triglyceride, serum HDL-C level, blood pressure, waist circumference were assessed and compared between groups by chi-square (x2) tests and unpaired student's 't' test as appropriate. A p value